INDUSTRY 4.0 FOR THE SMALL AND MEDIUM-SIZED ENTERPRISES IN THE MALAYSIAN CONSTRUCTION INDUSTRY - Mohd Afiq Azinuddin Bin Tayib,; Nor Azmi Bakhary,; Che Khairil Izam Che Ibrahim,; Nur Kamaliah Mustaffa, (Journal of Surveying, Construction and Property, 2022)
Industry 4.0 (IR 4.0) is becoming a trend in a plethora of sectors despite being used for the manufacturing industry. The concept has even attracted the attention of the construction sector yet despite that, the construction industry still favours conservative technology and is reluctant in incorporating new concepts into their practices. In order to adopt this concept for the construction industry, the main focuses should be placed upon the small and medium-sized enterprises (SMEs) since they act as a critical part in influencing the economy. Thus, the objectives of this paper are to determine the challenges faced by SMEs in adopting IR 4.0 in the Malaysian construction industry, propose the enablers of IR 4.0 for the Malaysian construction industry, investigate the readiness of SMEs in the Malaysian construction industry and identify the methods to successfully implement IR 4.0 for the construction SMEs. This study employed a survey questionnaire distributed amongst 380 local contractors and consultants around the Klang Valley and the collected data shall be analysed for descriptive statistics. The survey questionnaire had a 40.3% response rate and the results indicates that the main challenges in utilizing the IR 4.0 concept for the SMEs were the lack of financial resources, absence of a process change strategy and low experiences in utilizing skilled applications and technologies. The common enablers of IR 4.0 in the construction industry agreed by the respondents in the questionnaire were Building Information Modelling (BIM), modularization or prefabrication and augmented, virtual or mixed reality (AR/VR/MR). The readiness of the SMEs in implementing IR 4.0 were high in the aspects of modelling and simulation, prefabrication and having good access to internet. They agreed that having a regulatory framework and roadmaps for IR 4.0 adoption, doing necessary trainings to upskill and reskill, and strengthen the workforces’ knowledge in regards to IR 4.0 were one of the ways to improve the success for implementing IR 4.0. The results from this research will help to produce a robust framework later to hasten the adoption of IR 4.0 for the SMEs in the construction sector.